PERAN ROA, ROE, NPM DAN TATO SEBAGAI PREDIKTOR HARGA SAHAM PERUSAHAAN BLUE CHIP DI INDONESIA - Wulandari, Yesti; Rudianto, Totok; Sari, Dewi Maya; Arfiani, Mutia; Ramadhan, Rizki (E-Jurnal Akuntansi TSM, 2025)
This study aimed to analyze the effect of Return On Assets, Return On Equity, Net Profit Margin, and Total Asset Turnover on the stock prices of LQ45 companies. The population in this study consisted of 68 companies. Using the purposive sampling method, 24 companies were observed in this study. The data analysis method used was multiple linear regression analysis. The results of the study indicated that ROA, NPM, and TATO had a positive and significant effect on stock prices, while ROE did not have a significant effect on stock prices for LQ45 companies during the 2020-2024 period. Return on Assets, Return on Equity, Net Profit Margin, and Total Asset Turnover simultaneously influenced stock prices in LQ45 companies for the 2020-2024 period.